Intention to Use Digital Platforms for Islamic Financial Education in Malaysia: Structural Equation Model - Muhammad Zikry Hishamudin; Nur Shuhada Kamarudin; Noradilah Abdul Hadi; Azuan Ahmad (Semarak Ilmu Publishing, 2024)
Indexed by Scopus/MyCite